Fibrous material and method for manufacturing the same, and powder

CN123022849APending Publication Date: 2026-10-30TOYOTA BOSHOKU KK +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023061.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

另一方面,在复合材料用途中,例如,很久之前就已证实了纤维素纤维对于树脂是优异的增强材料,但实际情况是依然没有达到实际使用

Benefits of technology

[0030]根据本发明的纤维状物质,通过与以往不同的构成,从而包含纤维素纤维且能够在非水系中进行处理。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

To provide a fibrous substance containing cellulose fibers and capable of being handled in a non-aqueous system, a method for producing the same, and a powder, which are different from those of the past, the fibrous substance contains cellulose fibers and a water-soluble non-ionic compound interposed between the cellulose fibers, and the water-soluble non-ionic compound has a boiling point exceeding 100°C. The powder is formed by aggregation of the fibrous substance. The method for producing the fibrous substance includes a water removal step of removing water from a mixture containing the cellulose fibers, the water-soluble non-ionic compound, and water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to fibrous substances, methods for manufacturing the same, and powders. More specifically, it relates to fibrous substances utilizing cellulose fibers, methods for manufacturing the same, and powders. Background Technology

[0002] In recent years, cellulose fibers have been practically used in aqueous applications for purposes such as thickeners to regulate viscoelasticity. On the other hand, in composite material applications, for example, cellulose fibers have long been proven to be excellent reinforcing materials for resins, but practical application has not yet materialized. Thus, although cellulose fibers have shown excellent usefulness in composite material applications, practical use is still relatively rare. One reason for this is believed to be the strong hydrophilicity of cellulose fibers. Regarding this issue, the technologies described in Patent Documents 1-3 are known.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-148629

[0006] Patent Document 2: Japanese Patent Application Publication No. 2016-176052

[0007] Patent Document 3: Japanese Patent Application Publication No. 2019-189792 Summary of the Invention

[0008] The problem the invention aims to solve

[0009] Cellulose fibers are typically processed in an aqueous dispersion, but it is difficult to increase their solids concentration to over 60% by mass. The higher the degree of defibrillation of the cellulose fibers in the aqueous dispersion, the lower the solids concentration; typically, when it becomes a product known as nanocellulose, the solids concentration is less than 15% by mass. That is, processing is carried out in a situation where there is a significant amount of water compared to the target component. This is because cellulose, composed of polysaccharides, has a large number of hydroxyl groups derived from sugar chains, thus exhibiting strong hydrophilicity. For example, as mentioned above, even when resin blending is required, the presence of a large amount of water compared to the target component makes blending itself difficult, and even if blending is possible, water removal requires a huge energy cost. On the other hand, cellulose fibers have the property that when water is removed from an aqueous dispersion, as the amount removed increases, the cellulose fibers gradually aggregate / solidify strongly through hydrogen bonds. This property is extremely effective in papermaking, but it is impossible to form a dispersion in the absence of water. Therefore, there is a problem that cellulose fibers cannot be dispersed in a non-hydrophilic environment, nor can they be dispersed in resin. As mentioned above, cellulose fibers need to be handled in the presence of water, and there are many applications / uses that are hindered in practice due to operational difficulties such as agglomeration when trying to remove the dispersion medium.

[0010] In this regard, Patent Document 1 disclosed a technique for chemically modifying some of the hydroxyl groups in cellulose constituting nanocellulose by using an alkanoyl group having an alicyclic hydrocarbon group (

[0011] ) with the aim of providing novel modified nanocellulose and resin compositions comprising the same (

[0011] ).

[0011] In the aforementioned Patent Document 2, with the aim of providing a fiber-reinforced resin composition formed by appropriately compounding fibers with good dispersibility, and a method for manufacturing the same (

[0007] ), a fiber-reinforced resin composition is disclosed, which contains (A) chemically modified cellulose nanofibers and (B) thermoplastic resin, wherein the ratio R of the SP value of (A) to the SP value of (B) is 0.87 to 1.88, and the crystallinity of (A) is 42.7% or more ([claim 1], etc.). This disclosure mentions that by introducing alkyl groups such as acetyl groups (i.e., chemically modifying the hydroxyl groups), the hydroxyl groups of cellulose molecules are blocked, which can suppress the hydrogen bonding forces of cellulose molecules (

[0012] ).

[0012] In the aforementioned Patent Document 3, with the aim of providing modified cellulose nanofibers that can be mixed with thermoplastic resins in a dry powder state and have good compatibility and dispersibility with thermoplastic resins (

[0009] ), a modified cellulose nanofiber is disclosed, which comprises: cellulose nanofibers, a polycarboxylic acid bonded to the cellulose molecule, and a fatty acid polyvalent metal salt with 8 to 24 carbon atoms chelated with the carboxyl groups of the polycarboxylic acid other than the carboxyl groups bonded to the cellulose molecule ([claim 1] etc.).

[0013] The technologies described in patent documents 1-3 all eliminate the aforementioned problems by chemically modifying the hydroxyl groups derived from sugar chains. These technologies enable the processing of cellulose fibers in non-aqueous environments, thus resolving the problems encountered in resin compounding.

[0014] However, for example, in Patent Document 1, there is concern that a special alicyclic compound needs to be used as a chemical modifying agent, and in Patent Document 2, there is concern that the amount of organic solvent required during manufacturing, such as a total of 750 mL (Patent Document 1

[0445] ), is too large for 5 g of solid plant fiber. Furthermore, the technology in Patent Document 3 is based on chelation bonding with metal salts, and therefore has instability compared to chemical modification based on covalent bonds, raising concerns about the long-term stability, hydrolysis resistance, and resistance to catalyst decomposition caused by metal ions in the products obtained using this modified cellulose.

[0015] Thus, from the perspective of chemical modification of cellulose, various methods have been studied. However, it remains unclear which technology and solution is appropriate and whether it can be practically used. From the perspective of having more options for the future, there is a practical need for more different options.

[0016] The present invention was made in view of the above-mentioned actual situation, and its object is to provide a fibrous material, a method for manufacturing the same, and a powder thereof, wherein the fibrous material comprises cellulose fibers and can be processed in a non-aqueous system by means of a different composition than the conventional one.

[0017] Solution for solving the problem

[0018] That is, the present invention includes the following.

[0019] [1] A fibrous substance, characterized in that it comprises cellulose fibers and a water-soluble nonionic compound intermediate between the cellulose fibers.

[0020] The water-soluble nonionic compound has a boiling point exceeding 100°C.

[0021] [2] According to the fibrous material described in [1] above, wherein the solubility of the water-soluble nonionic compound relative to water is 0.5 g / 100 g H2O or more.

[0022] [3] According to the fibrous material described in [1] or [2] above, wherein when the total of the cellulose fibers and the water-soluble nonionic compound is set to 100% by mass, and the proportion of the cellulose fibers is set to R C The percentage by mass is set as R. W When the mass percentage is %, R C >R W .

[0023] [4] The fibrous material according to any one of [1] to [3] above, wherein the boiling point of the water-soluble nonionic compound is above 150°C and below 230°C.

[0024] [5] The fibrous material according to any one of [1] to [4] above, wherein the water-soluble nonionic compound is at least one of N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0025] [6] The fibrous material according to any one of [1] to [5] above is a modifier for thermoplastic resin.

[0026] [7] A method for manufacturing a fibrous material, which is the method for manufacturing a fibrous material according to any one of [1] to [6] above, characterized in that the method for manufacturing a fibrous material includes a water removal step for removing water from a mixture in which the cellulose fibers, the water-soluble nonionic compound and water coexist.

[0027] [8] According to the method for manufacturing the fibrous material described in [7] above, wherein when the total amount of the cellulose fibers and the water-soluble nonionic compound contained in the mixture is set to 100% by mass, and the proportion of the cellulose fibers is set to R C The percentage by mass is set as R. W When the mass percentage is %, R C >R W .

[0028] [9] A powder, characterized in that it is composed of an aggregate of fibrous material as described in any one of [1] to [6] above.

[0029] The effects of the invention

[0030] The fibrous material according to the invention, through a different composition than in the past, contains cellulose fibers and can be processed in a non-aqueous system.

[0031] The above-mentioned fibrous material can be obtained by the method for manufacturing fibrous material according to the present invention.

[0032] The powder according to the invention, through a different composition than in the past, contains cellulose fibers and can be processed in a non-aqueous system. Attached Figure Description

[0033] Figure 1 This is a graph showing the correlation between flexural modulus and Charpy impact strength related to Experimental Examples 2 and 4-6.

[0034] Figure 2 This is a graph showing the correlation between flexural modulus and Charpy impact strength related to Experimental Examples 1-3. Detailed Implementation

[0035] The matters illustrated herein are exemplary and intended to illustrate embodiments of the invention. They are set forth for the purpose of providing a description that enables the most efficient and readily understandable understanding of the principles and conceptual features of the invention. In this regard, this specification is not intended to go beyond the scope necessary for a fundamental understanding of the invention by describing the structural details of the invention in detail, but rather to illustrate to those skilled in the art, through description in conjunction with the accompanying drawings, how several embodiments of the invention are implemented in practice.

[0036] It should be noted that, unless otherwise specified, "XX~YY" in this instruction manual refers to "above XX and below YY". Additionally, "room temperature" refers to 25℃, and "normal pressure" refers to 1013.25 hPa.

[0037] [1] Fibrous material

[0038] The fibrous material of the present invention is characterized in that it comprises cellulose fibers and a water-soluble nonionic compound intermediate between the cellulose fibers.

[0039] The boiling points of the above-mentioned water-soluble nonionic compounds exceed 100°C.

[0040] The term "cellulose fiber" as used above refers to fibrous materials primarily composed of cellulose. It should be noted that, in this specification, cellulose fibers are described as follows, depending on the need: Cellulose fibers that serve as raw materials for fibrous substances and require coexistence with water to inhibit aggregation in the absence of water-soluble nonionic compounds are referred to as "aqueous cellulose fibers." Furthermore, cellulose fibers that constitute fibrous substances and do not require coexistence with water by coexisting with water-soluble nonionic compounds are referred to as "non-aqueous cellulose fibers." Moreover, when referring to both aqueous and non-aqueous cellulose fibers, the term "cellulose fiber" is used interchangeably.

[0041] Cellulose fibers typically have a maximum length of less than 1000 μm, further less than 500 μm, further less than 250 μm, and further less than 100 μm. There is no fixed lower limit; generally, a single cellulose fiber is 1 nm or longer, but can be 3 nm or longer, further 5 nm or longer, and further 10 nm or longer. These upper and lower limits can be appropriately combined. Therefore, for example, it can be set to 1 nm to 1000 μm, 3 nm to 500 μm, 5 nm to 250 μm, or 10 nm to 100 μm.

[0042] Specifically, examples include plant-derived fibers, pulp, cellulose microfibers, cellulose nanofibers (hereinafter also referred to as "CNF"), and lignocellulose (fibrous lignocellulose). Only one type can be used, or two or more types can be used together. Therefore, examples include CNF (fiber width of 3~100nm, aspect ratio of 10 or more, and length of 100μm or less) based on ISO / TS 20477:2017.

[0043] There are no restrictions on the source of cellulose fibers. Examples include cellulose fibers obtained from plants and cellulose fibers produced by microorganisms (bacterial cellulose). Only one type can be used, or two or more types can be used together.

[0044] Cellulose fibers obtained from plants can be cellulose fibers obtained from plants once, or cellulose fibers obtained again (two times, or multiple times) from items formed using cellulose fibers obtained once.

[0045] The source of the plant is not limited; it can be woody, herbaceous, or other plants such as bamboo and algae. As a woody plant, it can be any species including trees, shrubs, subshrubs, conifers, broad-leaved trees, evergreen trees, deciduous trees, and vines. Furthermore, the part of the plant is not limited; it can be any type of xylem, root, leaf, or bark. On the other hand, as a herbaceous plant, it can be any species including annuals, biennials, perennials, upright, creeping, and vines. Furthermore, the part of the herbaceous plant is not limited; it can be any type of stem, root, or leaf. Only one type can be used, or two or more types can be used together.

[0046] Examples of sources of further acquisition include cloth, fabrics, knitted fabrics, and paper. Only one type may be used, or two or more may be used together.

[0047] Plant-derived fibers can be substances that have been fiberized from plants in any way. Examples include plant-derived fibers fiberized by pulping, fiberized by retting, fiberized by microbial decomposition, and fiberized by enzymatic decomposition. Only one type of fiber may be used, or two or more types may be used together.

[0048] In the above, the plant-derived fibers that are fiberized through pulping (i.e., pulp) can be mechanically treated pulp (mechanical pulp (MP), groundwood pulp (GP), disc-milled mechanical pulp (RGP), thermomechanical pulp (TMP), etc.), chemically treated pulp (chemical pulp (CP), sulfate pulp (KP), sulfite pulp (SP), alkaline pulp (AP), etc.), or treated pulp possessing both characteristics (chemical groundwood pulp (CGP), semi-chemical pulp (SCP), etc.), or recycled pulp. Furthermore, it can be fiber pulp or dissolving pulp (DP). Only one type can be used, or two or more types can be used in combination.

[0049] Furthermore, as mentioned above, the source of the pulp is not limited; it can be wood pulp or non-wood pulp. Examples of wood pulp include softwood pulp (N-pulp) and hardwood pulp (L-pulp). Only one type can be used, or two or more types can be used in combination. Examples of non-wood pulp include cotton lint pulp, rag-pulp pulp, flax pulp, bagasse pulp, bamboo pulp, kenaf pulp, esparto pulp, hemp pulp, and straw pulp. Only one type can be used, or two or more types can be used in combination.

[0050] Furthermore, there is no limitation on whether the pulp is bleached or not. That is, it includes bleached hardwood sulfate pulp (LBKP), unbleached hardwood sulfate pulp (LUKP), bleached softwood sulfate pulp (NBKP), unbleached softwood sulfate pulp (NUKP), bleached hardwood sulfate pulp (LBSP), unbleached hardwood sulfate pulp (LUSP), bleached softwood sulfate pulp (NBSP), and unbleached softwood sulfate pulp (NUSP). Only one type can be used, or two or more types can be used in combination.

[0051] Furthermore, there are no restrictions on whether the pulp has been beaten or not. That is, it can be beaten pulp or unbeaten pulp. In the case of beaten pulp, it can be beaten pulp that has undergone free beating or beaten pulp that has undergone viscous beating. Only one type can be used, or two or more types can be used together. In addition, in the case of beaten pulp, there are no restrictions on its degree of freeness and degree of freeness (Canadian standard freeness [CFS]).

[0052] From the perspectives of reducing odor and improving heat resistance, dissolving pulp (DP) can be selected. Because dissolving pulp contains a high proportion of cellulose, it contains less lignin that decomposes under lower heating temperatures compared to non-dissolving pulp. Therefore, using dissolving pulp reduces odor compared to not using it. Furthermore, it provides superior heat resistance.

[0053] Here, odor refers to the smell produced by the decomposition of components that constitute cellulose fibers. For example, in a molded body obtained from a molding resin containing fibrous materials, heating (raising the temperature to a point where the resin can flow) occurs during molding of the molding resin, causing components that constitute cellulose fibers, such as lignin, to decompose. Therefore, the resulting molded body may sometimes produce an odor. In contrast, if DP pulp is used as the cellulose fiber, DP pulp contains less or no low-temperature decomposition components (such as lignin), so even after the aforementioned heating, no odor is produced, or even if an odor is produced, it can be reduced.

[0054] Furthermore, as an example of excellent heat resistance, a decrease in the temperature dependence of mechanical strength can be cited. That is, similarly to the above, in molded articles obtained from resins containing fibrous materials, lignin and the like are decomposed. Therefore, the mechanical strength of the resulting molded article sometimes exhibits a stronger temperature dependence. Specifically, an increase in the proportion of flexural modulus reduction with increasing temperature can be cited. In contrast, if DP pulp is used as the cellulose fiber, the amount of low-temperature decomposition components (lignin, etc.) contained in DP pulp is small or virtually non-existent; therefore, even after the aforementioned heating, the proportion of flexural modulus reduction is smaller than that of the former.

[0055] It should be noted that, as described above, cellulose fiber is a fibrous material mainly composed of cellulose. The proportion of cellulose contained in the cellulose fiber is not limited; for example, when the total cellulose fiber content is set at 100% by mass, it can be set to 40% by mass or more. When the cellulose fiber contains 40% by mass or more of cellulose, the effects of cellulose can be effectively obtained. This proportion is further preferably 50% by mass or more, and more preferably 60% by mass or more. Alternatively, this proportion can also be 100% by mass. It should be noted that the proportion of cellulose in the cellulose fiber is calculated by decomposing the insoluble components with alkali. Specifically, after soaking in a 17.5% NaOH aqueous solution for 2 hours, water of the same volume as the NaOH aqueous solution is added, and a boiling bath is performed for 1 hour. The dried residue (dried at below 80°C) in the resulting liquid is taken as cellulose. Furthermore, if the test object contains lignin, the lignin is decomposed and removed by chlorination before the amount of cellulose is measured. Specifically, the test object was immersed in a liquid composed of sodium chlorite and acetic acid in a mass ratio of 5:1 and heated to 80°C for 1 hour. The same operation was then performed on the filtered residue a total of 4 times to determine the amount of cellulose contained in the residue after lignin removal.

[0056] The number of cellulose fibers constituting fibrous substances is large. As long as the result is considered to be fibrous, determining the cellulose content of each individual cellulose fiber is not of substantial significance. Similarly, in cases using cellulose fibers from plant sources, the cellulose content varies depending on the source (type, part, etc.). Furthermore, depending on the degree of purification, there are those with higher and lower cellulose contents, which can be mixed and utilized. Therefore, as long as the result is considered to be fibrous, determining their average value is not of substantial significance.

[0057] It should be noted that fibrous material is only required to be defined as fibrous material, therefore it may or may not include hemicellulose, lignin and components derived from them.

[0058] Furthermore, the morphology of cellulose fibers is not limited other than being fibrous; specifically, an aspect ratio of 4 or higher is preferred. By having an aspect ratio of 4 or higher, the fibrous form of the fibrous material can be easily maintained. An aspect ratio of 5 or higher is further preferred, and more preferably 6 or higher. In addition, the aspect ratio is typically 10,000 or lower. It should be noted that the aspect ratio can be determined by measuring the maximum and minimum lengths of the cellulose fibers using an optical microscope or an electron microscope and calculating their ratio.

[0059] The number of cellulose fibers constituting the fibrous material is large, and as long as the result is considered to be fibrous material, determining the aspect ratio of each individual cellulose fiber is not of substantial significance. Similarly, when using cellulose fibers from plant sources, the aspect ratio varies depending on the source (type, part, etc.). Furthermore, depending on the processing method, there may be fibers with large aspect ratios and those with small aspect ratios, which can be mixed and utilized. Therefore, as long as the result is considered to be fibrous material, determining their average value is not of substantial significance.

[0060] The aforementioned "water-soluble nonionic compound" is a compound that is soluble in water, is nonionic, and has a boiling point exceeding 100°C (a temperature exceeding 100°C).

[0061] As mentioned above, aqueous cellulose fibers are fibrous materials that require coexistence with water to inhibit aggregation in the absence of water-soluble nonionic compounds. In this respect, water-soluble nonionic compounds can dissolve in the water coexisting with aqueous cellulose fibers, thus enabling a dispersed coexistence of cellulose fibers, water, and water-soluble nonionic compounds.

[0062] Furthermore, since the boiling point of water-soluble nonionic compounds exceeds 100°C, solvent removal using the boiling point difference from a state where water and water-soluble nonionic compounds coexist can preferentially remove water, which has a relatively low boiling point. As a result, water can be removed from a mixture containing cellulose fibers, water, and water-soluble nonionic compounds, forming a fibrous material in which non-aqueous cellulose fibers and water-soluble nonionic compounds coexist.

[0063] Furthermore, the water-soluble nonionic compound is a water-soluble and nonionic compound. That is, it is a compound that can dissolve in water without ionization. By making the compound nonionic, when water is removed from the mixture of cellulose fibers, water, and the water-soluble nonionic compound, it remains in the gaps between the cellulose fibers, thereby preventing the cellulose fibers from agglomerating. As a result, the cellulose fibers do not agglomerate and can form a dispersed state, i.e., a fibrous substance. In addition, the fibrous substance can be obtained in the above form without chemically bonding (chemical reaction) between the water-soluble nonionic compound and the cellulose fibers or their constituent components.

[0064] That is, by utilizing the interpenetration structure between aqueous cellulose fibers through which water-soluble nonionic compounds penetrate, it is possible to obtain non-aqueous cellulose fibers, i.e. fibrous substances, that can maintain a dispersed state without coexisting with water, without chemical bonds, using aqueous cellulose fibers that cannot maintain a dispersed state without coexisting with water as raw materials.

[0065] As a result, aqueous cellulose fibers require processing as a liquid or fluid, while fibrous materials can be processed as powder. Furthermore, aqueous cellulose fibers require a large amount of water, whereas fibrous materials do not, thus achieving a significant reduction in mass during cellulose fiber processing. Moreover, due to the removal of water, refrigeration is unnecessary, allowing for storage at room temperature and pressure. Therefore, pulverization significantly improves the workability of cellulose fibers.

[0066] As described above, the water-soluble nonionic compound does not bind to the cellulose fibers within the fibrous material of the present invention (no IR shift due to chemical bonds was confirmed), thus hindering the aggregation of the cellulose fibers. Therefore, it is considered that the aforementioned cellulose fibers and the water-soluble nonionic compound at least form a structure of mutual intrusion (interpenetration structure), but this interpenetration structure is considered to be obtained through a coating structure in which the water-soluble nonionic compound covers the cellulose fibers. This is derived from the excellent dispersibility of the fibrous material of the present invention within resins. In other words, the fibrous material of the present invention, by having a coating structure in which the water-soluble nonionic compound covers the periphery of the cellulose fibers, can achieve excellent dispersibility with resins.

[0067] Examples of such water-soluble nonionic compounds include pyrrolidone compounds, formamide compounds, acetamide compounds, alcohol compounds, sulfoxides, and ketones. Only one type of these compounds may be used, or two or more may be used in combination.

[0068] Examples of pyrrolidone compounds include 2-pyrrolidone and N-methyl-2-pyrrolidone derivatives. They can be used in combination with one or more of these compounds.

[0069] Examples of formamide compounds include formamide, N,N-dimethylformamide, and other formamide derivatives. They can be used in combination with one or more of these compounds.

[0070] Acetamide compounds include acetamide and acetamide derivatives such as 2-chloroacetamide and N,N-dimethylacetamide, as well as polymers such as poly-N-vinylacetamide. They can be used in combination with one or more compounds.

[0071] Examples of alcohol compounds include monohydric alcohols such as n-butanol, dihydric alcohols such as ethylene glycol, diethylene glycol, and propylene glycol, and polymers such as polyethylene glycol and polypropylene glycol. Only one type of alcohol may be used, or two or more may be used in combination.

[0072] Examples of sulfoxides include dimethyl sulfoxide. They can be used in single-component or multi-component combinations of two or more.

[0073] Examples of ketones include diethyl ketones. They can be used with only one type or with two or more types.

[0074] The water-soluble nonionic compound can be a solid at room temperature and pressure, but is preferably a liquid. When the water-soluble nonionic compound is a liquid at room temperature and pressure, it exhibits superior solubility and dispersibility in water coexisting with aqueous cellulose fibers compared to when it is a solid. That is, a small amount of the water-soluble nonionic compound can form the aforementioned interpenetrating structure, and a small amount of the water-soluble nonionic compound can be used to pulverize aqueous cellulose fibers into cellulose fiber powder. It should be noted that among the aforementioned water-soluble nonionic compounds, those that are solid at room temperature and pressure include acetamide, 2-chloroacetamide, poly-N-vinylacetamide, polyethylene glycol, and polypropylene glycol.

[0075] The degree of water solubility (relative to water solubility) of the water-soluble nonionic compound is not limited, but is preferably 0.05 g / 100 g H₂O or higher. That is, it is preferable that the water-soluble nonionic compound can dissolve 1% by mass or more of a coexistence of aqueous cellulose fibers and water (aqueous dispersion of aqueous cellulose fibers) with a solid content of 5% by mass. From the viewpoint of dispersibility, a higher solubility is preferred. That is, from the viewpoint of excellent dispersibility when dissolved in the coexistence, a higher solubility is preferred, for example, it can be set to 0.5 g / 100 g H₂O or higher, 5 g / 100 g H₂O or higher, 50 g / 100 g H₂O or higher, or 100 g / 100 g H₂O or higher.

[0076] On the other hand, there is no upper limit to the solubility in water; in fact, there is no limitation. That is, when the water-soluble nonionic compound is a solid, it can have a solubility similar to acetamide, which is twice the amount of water present, i.e., a solubility of 200 g / 100 g H2O. When the water-soluble nonionic compound is a liquid, it can have a solubility similar to N,N-dimethylacetamide, which is miscible with water.

[0077] Therefore, as described above, from the viewpoint of preferring higher solubility, among the water-soluble nonionic compounds exemplified above, liquids miscible with water are preferred. Therefore, 2-pyrrolidone, N-methyl-2-pyrrolidone, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethylene glycol, diethylene glycol, and propylene glycol are preferred. Only one of these compounds may be used, or two or more may be used in combination.

[0078] It should be noted that the solubility of water can be obtained from values ​​recorded in various databases (MERCK INDEX (https: / / merckindex.rsc.org / ) etc.).

[0079] As mentioned above, the boiling point of the water-soluble nonionic compound only needs to be above 100°C, but from the viewpoint of making separation from water easier, a greater difference in boiling point is preferred. For example, the boiling point of the water-soluble nonionic compound is preferably above 125°C, preferably above 150°C, preferably above 160°C, preferably above 170°C, preferably above 180°C, and preferably above 190°C.

[0080] On the other hand, while there is no upper limit to the boiling point of water-soluble nonionic compounds, when considering their use as modifiers in resin blending, it is preferable that they can be evaporated by heating during mixing (melt mixing, etc.), thereby further reducing the content contained within the resulting product. From this perspective, the boiling point of the water-soluble nonionic compound is preferably below 280°C, preferably below 250°C, preferably below 230°C, and preferably below 210°C.

[0081] These upper and lower limits can be appropriately set in various combinations. Therefore, the boiling point of a water-soluble nonionic compound can be set, for example, to 125~280℃, to 125~250℃, to 150~250℃, to 150~210℃, or to 160~230℃.

[0082] Therefore, within the aforementioned range, examples of water-soluble nonionic compounds having a boiling point in the range of 150 to 250°C include 2-pyrrolidone (boiling point 245°C), diethylene glycol (boiling point 244.3°C), formamide (boiling point 210°C), N-methyl-2-pyrrolidone (boiling point 202°C), ethylene glycol (boiling point 197.3°C), dimethyl sulfoxide (boiling point 189°C), propylene glycol (boiling point 188.2°C), N,N-dimethylacetamide (boiling point 165°C), and N,N-dimethylformamide (boiling point 153°C). In addition, examples of water-soluble nonionic compounds with boiling points in the range of 150~210℃ include formamide (boiling point 210℃), N-methyl-2-pyrrolidone (boiling point 202℃), ethylene glycol (boiling point 197.3℃), dimethyl sulfoxide (boiling point 189℃), propylene glycol (boiling point 188.2℃), N,N-dimethylacetamide (boiling point 165℃), and N,N-dimethylformamide (boiling point 153℃).

[0083] It should be noted that the boiling point value can be obtained from values ​​recorded in various databases (MERCK INDEX (https: / / merckindex.rsc.org / ) etc.).

[0084] The fibrous material only needs to contain cellulose fibers and water-soluble nonionic compounds, and their quantitative ratio is not limited. Let the total of cellulose fibers and water-soluble nonionic compounds be 100% by mass, and let the proportion of cellulose fibers be R.C The percentage by mass is set as R, where R represents the proportion of water-soluble nonionic compounds. W When the mass percentage is %, R is preferred. C >R W That is, compared to (R) C / R W R is preferred. C / R W >1. Through R C / R W >1, which can suppress the amount of water-soluble nonionic compounds used.

[0085] The ratio (R) C / R W The lower limit of (R) can be set to 1.1 or higher, 1.3 or higher, 1.5 or higher, 2.0 or higher, 3.0 or higher, 5.0 or higher, or 7.5 or higher. On the other hand, this ratio (R) C / R W The upper limit of ) can be set below 10000, below 1000, below 500, below 100, below 50, below 25, or below 15. These upper and lower limits can be appropriately set in various combinations. Therefore, for example, it can be set to 1.0 ≤ R. C / R W ≤10000, can be set to 1.1≤R C / R W ≤1000, can be set to 1.1≤R C / R W ≤500, can be set to 1.5≤R C / R W ≤100, can be set to 2.0≤R C / R W ≤50, can be set to 3.0≤R C / R W ≤25, can be set to 5.0≤R C / R W ≤15, can be set to 7.5≤R C / R W ≤15.

[0086] The water content (moisture content) in the fibrous material can be set to 0%. The fibrous material can exist essentially as a powder. Within this range, the presence of water is not impeded, and the water content in the fibrous material can also exceed 0%. In the fibrous material (and, moreover, the powder described later), when the total mass of the fibrous material is set to 100% by mass, the water content can be set to, for example, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, 5% by mass or less, or 1% by mass or less.

[0087] Cellulose is inherently hydrophilic. Furthermore, within fibrous materials, the water-soluble nonionic compounds that inhibit the aggregation of cellulose fibers do not exert their effect by bonding with the hydroxyl groups present in cellulose; therefore, it is believed that the hydroxyl groups present in cellulose are present in the same way as in aqueous cellulose fibers. Thus, fibrous materials and powders as aggregates of these materials are considered to be hygroscopic.

[0088] The uses of fibrous materials are not limited; for example, they can be used as modifiers or carriers for additives.

[0089] In the above, the modifier is a component that can modify the properties of other materials by compounding them. Since fibrous materials contain cellulose fibers, by compounding them with a modifier for fiber-reinforced resins, i.e., the resin raw material for molding, a modifier that improves the mechanical strength properties of the molded article obtained from the compounded resin for molding can be produced. Examples of mechanical strength properties include an increase in flexural modulus. Furthermore, examples include an increase in impact resistance, used to suppress the decrease in impact resistance that occurs with an increase in flexural modulus.

[0090] When fibrous materials are blended into resin raw materials for molding articles, the mechanism by which the resulting resin for molding articles achieves the effect of suppressing the reduction of impact resistance is not yet certain, but the following mechanism can be considered. That is, as mentioned above, the fibrous material contains water-soluble nonionic compounds intermediate between cellulose fibers. Microscopic observation of this situation reveals that the water-soluble nonionic compounds coat each cellulose fiber. Furthermore, it is believed that when the fibrous material is blended into the resin raw material for molding articles, through heating during resin mixing, some or all of the water-soluble nonionic compounds evaporate, forming gaps between the cellulose fibers and the matrix (e.g., resin) within the contained matrix. It is believed that such gaps reduce the point of failure compared to the case where the cellulose fibers are contained in contact with the matrix. Therefore, it is considered that the effect of suppressing the reduction of impact resistance can be achieved.

[0091] Furthermore, by using resin raw materials for coatings as modifiers in formulation, the viscosity of the coating obtained from the formulated resin can be modified. Examples of viscosity modification include thickening, imparting thixotropy, or reinforcement. Similarly, by formulating resin raw materials for adhesives, the viscosity of the adhesive obtained from the formulation can be modified. Examples of viscosity modification include thickening, imparting thixotropy, or reinforcement.

[0092] Additionally, a carrier for additives is a container used when additives are added to other materials. There are no restrictions on the types of additives; examples include flame retardants, flame retardant auxiliaries, fillers, colorants, antibacterial agents, and antistatic agents. Only one type can be used, or two or more can be used in combination.

[0093] In the above-mentioned applications, fibrous materials can be appropriately used as modifiers and carriers for additives. Furthermore, the types of other materials mentioned are not limited; examples include resins (thermoplastic resins, curable resins), thermoplastic elastomers, and rubber. Only one type may be used, or two or more may be used in combination. It is preferable to use thermoplastic resins and / or thermoplastic elastomers as other materials. Examples of such other materials include thermoplastic polyolefin resins and / or thermoplastic polyolefin elastomers.

[0094] The types of olefins constituting the aforementioned thermoplastic polyolefin resins and thermoplastic polyolefin elastomers are not limited, and examples include ethylene, propylene, 4-carbon olefins (1-butene, etc.), 5-carbon olefins (3-methyl-1-butene, 1-pentene, etc.), 6-carbon olefins (3-methyl-1-pentene, 4-methyl-1-pentene, 1-hexene, etc.), and 8-carbon olefins (1-octene, etc.). Only one type may be used, or two or more types may be used in combination.

[0095] Therefore, examples of polyolefins include polyethylene, polyethylene copolymers, polypropylene, polypropylene copolymers, polybutene, and polybutene copolymers. These polymers can be used in combination with only one type or in combination with two or more types. Furthermore, when there are two or more types, this includes both particles formed from mixed resins and mixtures of particles.

[0096] As mentioned above, polyethylene can be exemplified by ethylene homopolymers and copolymers of ethylene with olefins having 3 or more carbon atoms. Examples of the latter include ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-hexene copolymers, and ethylene-octene copolymers. Furthermore, copolymers of ethylene with other olefins can be random copolymers or block copolymers. It should be noted that, in copolymers of ethylene with other olefins, at least 50% of the total structural units are derived from ethylene.

[0097] Additionally, plant-derived polyethylene (hereinafter also referred to as "plant-derived PE") with a bio-based carbon content of 80% or higher, based on ISO 16620-2, can be used as polyethylene. This bio-based carbon content is based on... 14 The proportion of carbon in the total carbon composition is used to calculate the plant-derived carbon content (bio-based carbon content).

[0098] When using plant-derived PE, a bio-based carbon content of 80% or higher is preferred (100% is acceptable), and plant-derived PE of 85% or higher, and further, 90% or higher, can be used. In addition to ISO 16620-2, the bio-based carbon content can also be determined using values ​​based on the ASTM D6866 standard. Generally, the values ​​based on these standards are substantially the same.

[0099] Plant-derived polyethylene (PE) is a polymer with a backbone consisting of methylene (-CH2-) linked structures (methylene chains). Methylene chains are particularly derived from structural units of ethylene.

[0100] Furthermore, plant-derived PE includes ethylene homopolymers and copolymers of ethylene with other olefins. Only one type may be used, or two or more may be used in combination. When the plant-derived PE is a copolymer, the non-ethylene-derived units (units derived from other olefins) are preferably 50% or less (further, 30% or less, further, 10% or less) of the total number of structural units. This is because a low proportion of non-ethylene-derived units increases the bio-based carbon content. That is, for plant-derived PE, a low proportion of non-ethylene-derived units (e.g., 10% or less) is preferable to a substantial ethylene homopolymer.

[0101] Other examples of olefins include 3-carbon olefins (propylene), 4-carbon olefins (1-butene, etc.), 5-carbon olefins (3-methyl-1-butene, 1-pentene, etc.), 6-carbon olefins (3-methyl-1-pentene, 4-methyl-1-pentene, 1-hexene, etc.), and 8-carbon olefins (1-octene, etc.). Only one type can be used, or two or more types can be used together.

[0102] There are no limitations on the properties of plant-derived PE, but a density of 0.942 g / cm³ is preferred. 3The above refers to high-density polyethylene. Furthermore, the MFR (230°C / 2.16 kg) of plant-derived PE is preferably 35 g / 10 minutes or less, can be set to 20 g / 10 minutes or less, and further can be set to 15 g / 10 minutes or less. There is no limitation on the lower limit, but from the viewpoint of ease of melt mixing, it is preferably 2 g / 10 minutes or more, and can be set to 3 g / 10 minutes or more. The MFR (230°C / 2.16 kg) of plant-derived PE is a value determined according to ISO 1133 or ASTM D1238 standards. These specifications are generally substantially the same.

[0103] As mentioned above, the preferred density of plant-derived PE is 0.942 g / cm³. 3 The above can be set to a density of 0.950 g / cm³. 3 The above. There is no upper limit to the density, but 0.954 g / cm³ is preferred. 3 The density of polyethylene is a value determined according to ISO 1183 or ASTM D792 standards. These values ​​are generally substantially the same.

[0104] The balance between MFR and density can be achieved by adjusting the linearity, branching amount, and molecular weight of polyethylene.

[0105] In the above examples, polypropylene can be exemplified by propylene homopolymers and copolymers of propylene with other olefins. Examples of the latter include propylene-ethylene copolymers, propylene-butene copolymers, propylene-hexene copolymers, and propylene-octene copolymers. Furthermore, copolymers of propylene with other olefins can be random copolymers or block copolymers.

[0106] From the perspective of excellent elastomer properties, propylene-ethylene copolymers can be utilized. Propylene-ethylene copolymers are block copolymers of polypropylene with ethylene blocks as the dispersed phase. That is, they are polypropylene resins with homopolymer polypropylene as the continuous phase and a dispersed phase containing polyethylene within this continuous phase. Copolymers of polypropylene with such ethylene blocks as the dispersed phase are also known as impact copolymers, polypropylene impact copolymers, multiphase polypropylene, multiphase block polypropylene, etc. It should be noted that in copolymers of propylene and other olefins, more than 50% of the total number of structural units are derived from propylene.

[0107] It should be noted that the properties of polyolefins used as other materials are not limited; for example, in the case of polypropylene, a density of 0.85~0.95 g / cm³ can be used. 3 (Therefore, the density is 0.88~0.92 g / cm³) 3The polypropylene is a compound with a median flow rate (MFR) of 15 g / 10 minutes or higher. Excellent impact resistance can be obtained when the MFR of polypropylene is 15 g / 10 minutes or higher (typically 100 g / 10 minutes or lower). This MFR can be further set to 20 g / 10 minutes or higher, or even 25 g / 10 minutes or higher. There is no upper limit, but from the viewpoint of ease of mixing, it can be set to 80 g / 10 minutes or lower, or even 50 g / 10 minutes or lower.

[0108] It should be noted that the MFR (230℃ / 2.16kg) of polyolefins was determined according to ISO 1133. Furthermore, a balance between MFR and density can be achieved by adjusting the linearity, branching amount, and molecular weight of the polyolefin.

[0109] [2] Powder

[0110] The powder of this invention is composed of fibrous materials.

[0111] Regarding fibrous substances, as described above.

[0112] As described above, the powder of the present invention contains cellulose fibers, but due to the coexistence of water-soluble nonionic compounds, it can be processed in a non-aqueous system. Therefore, it can also be formulated for resins that require non-aqueous processing. That is, it can be dispersedly contained within the resin. Therefore, a reinforced resin reinforced with fibrous materials can be obtained. More specifically, for resins that have conventionally been reinforced with reinforcing agents such as glass fibers, whiskers, and fibrous fillers, these reinforcing agents can be substituted or mixed with these conventional reinforcing agents into the resin.

[0113] Furthermore, resins (molded articles) formulated with these reinforcing agents are sometimes difficult to reuse. This is because, in the past, when reinforcing agents were to be reused, they were destroyed during compounding, resulting in a reduced aspect ratio and thus a decreased reinforcing effect. In this regard, since the powder of the present invention is formed from cellulose and a water-soluble nonionic compound, it possesses flexibility. Therefore, it is less prone to destruction during compounding for reuse, and the reduction in aspect ratio can be significantly suppressed. Therefore, the reusability of reinforced resins using the powder of the present invention as a reinforcing agent is excellent.

[0114] [3] Methods for manufacturing fibrous materials

[0115] The method for manufacturing fibrous materials according to the present invention is characterized by a water removal step that removes water from a mixture in which cellulose fibers, a water-soluble nonionic compound and water coexist.

[0116] The “water removal process” is the process of removing water from a mixture containing cellulose fibers, water-soluble nonionic compounds and water.

[0117] Regarding cellulose fibers and water-soluble nonionic compounds, as described above.

[0118] In the water removal process, water can be removed by any method. Examples of removal methods include evaporation-based removal, centrifugation-based removal, and compression-based removal. Only one method may be used, or two or more may be used in combination.

[0119] Evaporation is preferred. As described above, the water-soluble nonionic compound is a compound that is both water-soluble and nonionic, and has a boiling point exceeding 100°C. Therefore, by utilizing evaporation, the water-soluble nonionic compound can remain in the mixture, while water with a lower boiling point than the water-soluble nonionic compound is preferentially removed.

[0120] In the water removal process, water removal can be either a portion or all of the water contained in the mixture. That is, the water removal rate can be 100% or less than 100%. This is because the moisture content of the obtained fibrous material can be 0%, but as long as it can exist as a powder, the moisture content can also exceed 0%. Specifically, as described above, in the obtained fibrous material, when the total mass of the fibrous material is set to 100% by mass, the water content can be set to 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, 5% by mass or less, or 1% by mass or less.

[0121] It should be noted that the moisture content can be measured using an infrared moisture meter at a drying temperature of 105℃ and a drying time of 5 hours.

[0122] The mixture can be formed before or simultaneously with the water removal process. That is, in the case of a mixture forming process, the mixture forming process can be set before the water removal process, can be performed simultaneously with the water removal process, or can be both.

[0123] Simultaneous mixing and water removal processes can be illustrated by cases where the mixing process and water removal within the mixture occur concurrently. For example, cases where components constituting the mixture are added during the water removal process can be cited. Specifically, cases where a water-soluble nonionic compound is added to a coexistence of aqueous cellulose fibers and water while water removal is performed simultaneously can be cited. Furthermore, cases where water is added to a coexistence of aqueous cellulose fibers and water while water removal is performed simultaneously can be cited. As for the latter, for example, when dry pulp is used as a raw material for aqueous cellulose fibers, processes such as adding water to more reliably dissociate the cellulose fibers, or adding water while beating to increase the degree of beating (increasing the degree of defiberization) can be cited. In this way, by improving the dissociation state of the cellulose fibers, the cross-intrusion caused by the water-soluble nonionic compound can be obtained more reliably.

[0124] The mixture can be formed as long as it creates a state in which cellulose fibers, a water-soluble nonionic compound, and water coexist. The method of formation is not limited. For example, it can be obtained by (1) mixing aqueous cellulose fibers (containing cellulose fibers and water) with a water-soluble nonionic compound. Alternatively, it can be obtained by (2) mixing cellulose fibers, water, and a water-soluble nonionic compound. Furthermore, it can be obtained by (3) mixing cellulose fibers with a mixture containing a water-soluble nonionic compound and water. Furthermore, in the case of (1) above, the mixture can be carried out while adding a water-soluble nonionic compound to the aqueous cellulose fibers, or while adding a mixture of a water-soluble nonionic compound and water to the aqueous cellulose fibers. Only one of these methods can be used, or two or more can be used together.

[0125] Furthermore, as a method of forming a mixture simultaneously with the water removal process (the water removal process and the mixture formation process are performed concurrently), examples include adding components constituting the mixture during the water removal process. That is, examples include continuously adding water-soluble nonionic compounds during the water removal process.

[0126] Furthermore, when the water content in the aqueous cellulose fibers used as raw materials is reduced, a pretreatment can be performed by adding water to more reliably dissociate the cellulose fibers contained in the aqueous cellulose fibers. By utilizing a mixture that improves the dispersibility of the cellulose fibers contained in the aqueous cellulose fibers, the cross-penetration based on water-soluble nonionic compounds can be obtained more reliably.

[0127] The amount of water-soluble nonionic compound contained in the mixture is not limited; as a result, any amount of the aforementioned fibrous material is acceptable. Generally, the mixture can be blended in a ratio that determines the proportion of cellulose fibers to the water-soluble nonionic compound in the resulting fibrous material. That is, as described above, the total amount of cellulose fibers and the water-soluble nonionic compound is set at 100% by mass, and the proportion of cellulose fibers is set at R. C The percentage by mass is set as R, where R represents the proportion of water-soluble nonionic compounds. W When the mass percentage is %, R is preferred. C / R W >1, its lower limit can be set to 1.1 or higher, 1.3 or higher, 1.5 or higher, 2.0 or higher, 3.0 or higher, 5.0 or higher, or 7.5 or higher. On the other hand, this ratio (R) C / R W The upper limit of ) can be set below 10000, below 1000, below 500, below 100, below 50, below 25, or below 15. These upper and lower limits can be appropriately set in various combinations. Therefore, for example, it can be set to 1.0 ≤ R. C / R W ≤10000, can be set to 1.1≤R C / R W ≤1000, can be set to 1.1≤R C / R W ≤500, can be set to 1.5≤R C / R W ≤100, can be set to 2.0≤R C / R W ≤50, can be set to 3.0≤R C / R W ≤25, can be set to 5.0≤R C / R W ≤15, can be set to 7.5≤R C / R W ≤15.

[0128] For example, a step can be included where water-soluble nonionic compounds are removed in appropriate proportions after water is removed by evaporation. With such a water-soluble nonionic compound removal step, a large quantity of water-soluble nonionic compounds can be mixed regardless of the aforementioned mixing ratio.

[0129] The mixture can be mixed using any device, such as a mixer, kneader, extruder, kneader, or agitator (high-speed flow mixer, paddle mixer, ribbon mixer, etc.). Only one type can be used, or two or more can be used in combination. Furthermore, when using two or more types, the operation can be continuous or intermittent (batch-type). Moreover, the raw materials can be mixed together or added in multiple stages (multi-stage mixing). Additionally, if these devices have a screw, they can be single-shaft, dual-shaft, or multi-shaft, with dual-shaft being preferred.

[0130] In the water removal process, when evaporation is used in water removal, it can be carried out under any conditions, such as atmospheric pressure, pressurized pressure, or depressurized pressure, or a combination thereof. From the point of view of energy cost, evaporation by depressurization (depressurized evaporation) is preferred because it can reduce the heating temperature.

[0131] The pressure reduction conditions can be set to an appropriate range depending on the water-soluble nonionic compound used. Similarly, the heating conditions can also be set to an appropriate range depending on the water-soluble nonionic compound used; for example, they can be set above 90°C, above 100°C, or above 120°C. There is no upper limit; typically, they can be set below 250°C or below 200°C. These upper and lower limits can be appropriately combined. Therefore, for example, they can be set to 90~250°C, 100~200°C, or 120~200°C.

[0132] It should be noted that, as needed, a process for removing water-soluble nonionic compounds can be added after the water removal process. The removal of water-soluble nonionic compounds can be limited to a portion or all of the water-soluble nonionic compounds contained in the resulting cellulose fiber powder. Furthermore, water-soluble nonionic compounds can be removed by any means; similar to water removal, they can be removed by evaporation. In this case, after the water is removed by evaporation, the removal of water-soluble nonionic compounds can continue by evaporation.

[0133] Furthermore, when a water-soluble nonionic compound removal process is included, regardless of the mixing ratio (content ratio) of the cellulose fiber and the water-soluble nonionic compound, the cellulose fiber powder can contain more water-soluble nonionic compounds.

[0134] As described above, processes such as water removal and mixture formation can be included, but other processes may also be included. One example of such other processes is a purification process for purifying cellulose fibers. The purification process is a process for purifying cellulose fibers, and can be, for example, a process for increasing cellulose concentration or a process for increasing the degree of beating. The purification process is preferably performed before the mixture formation process.

[0135] Example

[0136] The present invention will be specifically described below through examples.

[0137] [1] Manufacturing of fibrous materials

[0138] (1) Components of each raw material

[0139] (1-1) Microfibrillated cellulose (tiny fibrous cellulose), solid content concentration 14.4% by mass, product name "CELISH KY 110N" (manufactured by Daicel Miraizu Co., Ltd.)

[0140] (1-2) Water-soluble nonionic compounds

[0141] “NMP”: N-methyl-2-pyrrolidone

[0142] "DMF": N,N-Dimethylformamide

[0143] “DMAc”: N,N-dimethylacetamide

[0144] DMSO: Dimethyl sulfoxide

[0145] (2) Using the device

[0146] An apparatus is prepared having a reaction vessel capable of performing mixing, kneading, and vacuum distillation operations individually or simultaneously within the reaction vessel. The apparatus has the following specifications: for mixing and kneading operations, it can use a three-arm agitator to mix the contents within the reaction vessel (motor performance: 0.75 kW - 4P - 200V - 60Hz - 39A - 1800 rpm / min), and can heat the reaction vessel to a maximum temperature of approximately 300°C using a heater sleeve wound around the outer periphery of the reaction vessel. Furthermore, the apparatus has the following specifications: for distillation operations, it can depressurize the pressure within the reaction vessel to a maximum of approximately 0.1 MPa using a connected vacuum pump, and can heat the reaction vessel to a maximum temperature of approximately 80°C using a heater sleeve wound around the outer periphery of the reaction vessel.

[0147] (3) As shown in Table 1, the two raw materials were added to the reaction vessel such that the solid content of cellulose fibers was 1 part by mass, 10 parts by mass, or 1000 parts by mass when each of the water-soluble nonionic compounds NMP, DMF, DMAc, and DMSO was set as 1 part by mass. Then, a vacuum evaporation operation was performed while the reactor was depressurized to 0.072 MPa, the stirrer was rotated at 20 Hz, and the temperature was heated to 120°C. After substantially all the water contained in the raw materials was evaporated, the apparatus was stopped, and the aggregates of fibrous materials, i.e., powders, of Experimental Examples 1 to 6, which were the reaction products, were taken out of the reaction vessel. In all cases, these reaction products were powders with a soft hand feel, i.e., powders of aggregates of fibrous materials.

[0148] (4) Determination of moisture content of fibrous materials

[0149] Regarding the fibrous materials (powder as an aggregate of fibrous materials) in Experiments 1-6, the moisture content was measured using an infrared moisture meter (model "FD-720", manufactured by Kett Scientific Research Institute Co., Ltd.) at a drying temperature of 105°C and a drying time of 5 hours. The results showed that the moisture content of any fibrous material was 0% (rounded to the nearest whole number).

[0150] [2] Preparation of molded articles for modification evaluation

[0151] The fibrous materials obtained in Experimental Examples 1 to 6 above [1] were mixed and contained in an olefin resin, and then injection molded to obtain the molded articles for evaluation. It should be noted that the amount of fibrous material added is as shown in Table 1.

[0152] As an olefin-based resin, a propylene block copolymer (manufactured by Nippon Polypropylene Co., Ltd., trade name "NOVATECBC6", MFR 2.7g / 10min, melting point 163℃) was used.

[0153] [3] Evaluation of molded bodies

[0154] (1) Determination of flexural modulus

[0155] Using the evaluation molded articles obtained in [2] above, tensile tests were performed according to ISO 527-1. The results are shown in Table 1 as “flexural elasticity”. It should be noted that the evaluation molded articles formed by injection molding consisting only of modified target resin (block PP) without the addition of fibrous composite were measured in the same manner as above, and the flexural modulus was 902 (MPa).

[0156] [Experimental Conditions]

[0157] Test: Autograph 50kN (manufactured by Shimadzu Corporation, model "AGS-X")

[0158] Test temperature: 23℃

[0159] Test piece shape: ISO multi-purpose test piece

[0160] Tensile speed (elastic modulus measurement): 1 mm / min

[0161] Drying conditions: Vacuum drying at 23℃ for 24 hours or more

[0162] (2) Determination of Charpy impact strength

[0163] Charpy impact strength tests were conducted using the evaluation molded articles obtained in [2] above (according to ISO 179). At this time, test pieces with notches (Type A) were used, and the tests were conducted by the side flexural strength test at a test temperature of 23°C. The results are presented as “Charpy” in Table 1. It should be noted that evaluation molded articles consisting only of modified target resin (block PP) without added fibrous composites, formed by injection molding, were also tested in the same manner as above, and the Charpy impact strength was 59.0 (kJ / m²). 2 ).

[0164] [Table 1]

[0165]

[0166] [4] Effects of the embodiment

[0167] (1) Based on the results in Table 1, the figures for Experiments 2, 4-6, which compared the ratio of water-soluble nonionic compound to cellulose fiber of 1:10, are presented in the figure. Figure 1 .Depend on Figure 1 It is known that even if any water-soluble nonionic compound among NMP, DMF, DMAc and DMSO is used, it can be easily dispersed in the matrix resin, and the flexural modulus improvement effect brought about by the blending of cellulose fibers can be significantly obtained.

[0168] Furthermore, when cellulose fibers are typically blended into resin for resin modification purposes, the resulting modified resin exhibits a significantly increased flexural modulus, but suffers a significant decrease in impact resistance—a trade-off between flexural modulus and impact resistance. Regarding this, it is evident that in Experimental Examples 2, 4-6, high impact resistance was maintained across the entire practical flexural modulus range, i.e., below 1900 MPa (high Charpy impact strength at the same flexural modulus). Specifically, when NMP (Experimental Example 2) or DMSO (Experimental Example 4) was used as the water-soluble nonionic compound, the impact resistance was maintained higher compared to when DMAc (Experimental Example 5) or DMSO (Experimental Example 6) was used as the water-soluble nonionic compound. That is, it is clear that the trade-off between flexural modulus and impact resistance can be more effectively suppressed. Furthermore, in Figure 1 From the data, it can be seen that the plotted data of NMP (Experimental Example 2) and DMSO (Experimental Example 4) have a flexural modulus of 1513 MPa and a Charpy impact strength of 19.47 kJ / m. 2 While there is a crossover at certain points, in the region below 1513 MPa, which can be considered a more practical range of flexural moduli, Experimental Example 2 is able to maintain Charpy impact strength most effectively.

[0169] (2) Compare the curves of experimental examples 1-3 on [the graph]. Figure 2 Examples 1-3 are examples of using fibrous materials that utilize the water-soluble nonionic compound NMP, which showed the best effect in (1) above, with a ratio of water-soluble nonionic compound to cellulose fiber of 1:1 to 1:1000. From these results, it can be seen that the effect of increasing flexural modulus is the best in Example 3. On the other hand, it can be seen that the effect of maintaining Charpy impact strength is the best in Example 1. Regarding this, it can be seen that the effect of suppressing the trade-off between flexural modulus and impact resistance is the best in Example 2 (achieving the highest Charpy impact strength at the same flexural modulus).

[0170] It should be noted that the present invention is not limited to the contents described in the specific embodiments above, and various modified embodiments may be provided within the scope of the present invention according to the purpose and use.

[0171] The examples above are for illustrative purposes only and are not intended to limit the invention. Examples of typical embodiments have been given to illustrate the invention; however, it is understood that the statements used in the description and illustrations of the invention are not limiting but descriptive and illustrative. As described in detail herein, modifications can be made within the scope or spirit of the appended claims without departing from the invention. Specific structures, materials, and embodiments are referred to in the detailed description of the invention herein, but it is not intended to limit the invention to the matters disclosed herein. Of course, the invention is intended to cover all functionally equivalent structures, methods, uses, etc., within the scope of the appended claims.

Claims

1. A fibrous substance, characterized in that, It comprises cellulose fibers and water-soluble nonionic compounds intermediate between the cellulose fibers. The water-soluble nonionic compound has a boiling point exceeding 100°C.

2. The fibrous material according to claim 1, wherein, The water-soluble nonionic compound has a solubility of more than 0.5 g / 100 g H2O relative to water.

3. The fibrous material according to claim 1, wherein, When the total amount of the cellulose fiber and the water-soluble nonionic compound is set to 100% by mass, and the proportion of the cellulose fiber is set to R... C The percentage by mass is set as R. W When the mass percentage is %, R C >R W .

4. The fibrous material according to claim 1, wherein, The boiling point of the water-soluble nonionic compound is above 150°C and below 230°C.

5. The fibrous material according to claim 1, wherein, The water-soluble nonionic compound is at least one of N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

6. The fibrous material according to claim 1, wherein it is a modifier for thermoplastic resins.

7. A method for manufacturing a fibrous material, comprising the method for manufacturing a fibrous material as described in claim 1, characterized in that, The method for manufacturing the fibrous material includes a water removal step for removing water from a mixture in which the cellulose fibers, the water-soluble nonionic compound, and water coexist.

8. The method for manufacturing the fibrous material according to claim 7, wherein, When the total amount of the cellulose fibers and the water-soluble nonionic compound contained in the mixture is set to 100% by mass, and the proportion of the cellulose fibers is set to R... C The percentage by mass is set as R. W When the mass percentage is %, R C >R W .

9. A powder, characterized in that, It is composed of an aggregate of fibrous material as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Modified nanocellulose, and resin composition containing modified nanocellulose

    JP2014148629A

  • Fiber reinforced resin composition containing chemical modified cellulose nanofiber and thermoplastic resin

    JP2016176052A

  • Modified cellulose nanofiber and manufacturing method therefor, thermoplastic resin composition, and molded body

    JP2019189792A